The Rohingya in South Asia : people without a state - Basu Ray Chaudhury, Sabyasachi; Samāddāra, Ran̤abīra (Routledge, 2018)
"The Rohingya of Myanmar are one of the world's most persecuted minority populations without citizenship. After the latest exodus from Myanmar in 2017, there are now more than half a million Rohingya in Bangladesh living in camps, often in conditions of abject poverty, malnutrition and without proper access to shelter or work permits. Some of them are now compelled to take to the seas in perilous journeys to the Southeast Asian countries in search of a better life. They are now asked to go back to Myanmar, but without any promise of citizenship or an end to discrimination. This book looks at the Rohingya in the South Asian region, primarily India and Bangladesh. It explores the broader picture of the historical and political dimensions of the Rohingya crisis, and examines subjects of statelessness, human rights and humanitarian protection of these victims of forced migration. Further, it chronicles the actual process of emergence of a stateless community - the transformation of a national group into a stateless existence without basic rights. This volume will be of great interest to students and researchers of human rights, migration and diaspora studies, race and ethnic studies, refugee studies, politics and international relations, discrimination studies, and peace and conflict studies, as well as to international organizations, those in law, media and journalism, civil society and policymakers"--Back cover.